Qualitative analysis for k-fractional integral boundary value problems of quasilinear equation with p-Laplacian operator - Bo Zhang; Xiaohui Shen; Tengfei Shen (Boundary Value Problems)
Abstract In this paper, we are devoted to considering the existence of solutions for k-fractional integral boundary value problems of Hadamard fractional order quasilinear equation with p-Laplacian operator. Based on the coincidence degree theory, some new results are presented. Moreover, an example is shown to verify our main conclusions.